2021
DOI: 10.1016/j.jamda.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Deprescribing With Reduction in Mortality and Hospitalization: A Pragmatic Stepped-Wedge Cluster-Randomized Controlled Trial

Abstract: Objectives: Deprescribing has gained awareness recently, but the clinical benefits observed from randomized trials are limited. The aim of this study was to examine the effectiveness of a pharmacist-led 5-step team-care deprescribing intervention in nursing homes to reduce falls (fall risks and fall rates). Secondary aims include reducing mortality, number of hospitalized residents, pill burden, medication cost, and assessing the deprescribing acceptance rate. Design: Pragmatic multicenter stepped-wedge cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 39 publications
0
54
1
Order By: Relevance
“…Suboptimal use of analgesics, inappropriate use of repeat prescriptions, and self‐medication with over‐the‐counter drugs together with prescribed analgesics, non‐adherence and adverse drug effects are some of the common issues that need a medication review 31 . The value of pharmacists in conducting medication reviews has been well established to optimize drug therapy and reduce drug‐related problems 30,32–34 . Pharmacist‐implemented pharmaceutical care plans 15,18,20 or use of educational videos 27 are some of the additional interventions to medication review that have been noted in this review.…”
Section: Discussionmentioning
confidence: 97%
“…Suboptimal use of analgesics, inappropriate use of repeat prescriptions, and self‐medication with over‐the‐counter drugs together with prescribed analgesics, non‐adherence and adverse drug effects are some of the common issues that need a medication review 31 . The value of pharmacists in conducting medication reviews has been well established to optimize drug therapy and reduce drug‐related problems 30,32–34 . Pharmacist‐implemented pharmaceutical care plans 15,18,20 or use of educational videos 27 are some of the additional interventions to medication review that have been noted in this review.…”
Section: Discussionmentioning
confidence: 97%
“…Deprescribing typically follows a formal medication review protocol, which is informed by one or more of the tools that are now available to help clinicians identify medications to target for reductiondmost notably the AGS Beers criteria and the STOPP/START Criteria. 57e59 This issue of JAMDA reports results from 2 deprescribing programs: a randomized trial in 4 Singapore nursing homes, which demonstrated reductions in pill burden, costs, hospitalizations, and mortality 60 ; and a preliminary report from Australia of an electronic system in an acute hospital that focused on deprescribing and was shown to lower overall drug burden and potentially inappropriate medications. 61 These and other studies indicate that although purists would advocate that "right prescribing" is the ultimate goal, deprescribing has gained a legitimate and useful role in medication management in post-acute and long-term care.…”
Section: Deprescribingmentioning
confidence: 99%
“…A possible solution for reducing inappropriate polypharmacy is called "deprescribing": a planned and supervised process of dose reduction or stopping of medication that might be causing harm, or no longer be of benefit (Scott et al, 2015). Kua et al (2021) determined the effect of a deprescribing intervention by means of a stepped-wedge cluster-randomized controlled trial and showed that deprescribing was associated with reductions in mortality and number of hospitalized residents in nursing homes (Kua et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… Kua et al (2021) determined the effect of a deprescribing intervention by means of a stepped-wedge cluster-randomized controlled trial and showed that deprescribing was associated with reductions in mortality and number of hospitalized residents in nursing homes ( Kua et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%